A Low-Cost Laboratory Practice for Fundamental Learning of Wireless Digital Communication - Titon Dutono; Tri Budi Santoso (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Several studies have shown that the main challenge in teaching complex systems involving many theoretical backgrounds to senior students is their lack of confidence. In this paper, we present an approach to the teaching methodology of an undergraduate course in a telecommunication study program. The first goal of this methodology is to help students understand the theoretical concepts behind wireless digital communication systems through direct practice to give them more exposure to a real system through affordable practice activities in an experiential context, utilizing an HF radio and a single-board computer (SBC). The second goal is to challenge senior students to understand the data link layer by using white box testing of the syntax of the programming language embedded in the SBC. This approach is ideally carried out based on offline and hands-on class activities, however, the pandemic condition made it unavoidable to do it online using a demonstration model. Feedback from students was collected through written comments, post-testing, including a facility index analysis, and a questionnaire that was distributed using the available e-learning system. The post-test results showed that the average score was 72 out of a maximum of 100.